Morphology and morphometric features of the cerebellum of poultry - Horalskyi, L. P.; Sokulskiy, I. M.; Kolesnik, N. L.; Gutyj, B. V.; Romaniuk, R. K.; Pavliuchenko, O. V.; Shevchuk, S. Y.; Maksymenko, Y. V. (Regulatory Mechanisms in Biosystems, 2024)
The connection of the cerebellum with the structural parts of the brain and the complex neural system of processing information coming to its cortex make it unique in terms of the variety of functions it performs. The cerebellum is not only the center of coordination of movements and balance but also participates in the regulation of many other functions of the body. The article presents research results into the macro- and microscopic structure and features of the morphometry of the cerebellum of poultry, which belong to the vertebrate subtype, class Aves – birds. For their implementation, the selected material (cerebellum, n = 6) was subjected to fixation in a 10–12% neutral formalin solution, followed by embedding in paraffin. From paraffin blocks, histological sections with no more than 10 μm thickness were made. Staining of tissue preparations with hematoxylin and eosin was used to study cell morphology, conduct morphometric studies, and obtain review histological sections, as well as neurohistological methods of impregnation of nerve tissue with silver nitrate according to Bolshovsky Gros and Ramon-i-Cajal. According to research results, the cerebellum in birds is located between the cerebrum and midbrain, dorsal to the medulla oblongata. The body and two (right and left) lateral ears form the cerebellum. The organ’s surface is divided into lobes by numerous furrows; the latter are united into three lobes: front, middle, and back. In the lateral projection, the cerebellum is triangular, with a ventrally elongated apex. In the birds we studied, the cerebellum is characterized by the general principles of its structural organization and morphotopography but differs in its organometallic indicators. According to organometry, the absolute mass of the cerebellum in poultry is different: the largest in turkeys, the smallest in geese, then in ducks, and the smallest in chickens. The relative mass of the cerebellum changes synchronously with the absolute mass and is 0.047% in turkeys, 0.041% in geese, 0.036% in ducks, and 0.023% in chickens. The microscopic structure of the cerebellum of domestic birds has a similar structural organization: gray (cortex) and white matter are differentiated on a cross-section. Molecular, ganglionic, and granular layers form gray matter. It is characterized by a heterogeneous population of neurocytes, which have a determined relationship between the level of the morphofunctional state of the nervous and innervated structures. According to the results of histometry, the thickness of the cerebellar cortex of birds is different: in chickens – 350.7 ± 12.68 μm, in turkeys – 404.25 ± 5.76, in ducks – 376.29 ± 5.34, in geese – 234.85 ± 2,43 μm. The most significant thickness in all birds is characteristic of the granular layer, somewhat smaller – molecular, and the smallest - in the ganglionic layers. According to the cytometry results, the smallest volume of Purkinje cells, characteristic of the cerebellum of the domestic chicken, is somewhat more significant for the domestic duck, followed by geese and turkeys. At the same time, the nuclear-cytoplasmic ratio of Purkinje cells has different values: the highest indicator is found in geese, approximately – in ducks and turkeys, significantly 1.75 times lower – in chickens. The conducted results expand and supplement the information on the macro- and microscopic structure of the cerebellum regarding the species characteristics of domestic birds, which is of relevance for anatomy, histology, comparative anatomy, forensic veterinary medicine, zoology, etc.